An Exploratory Analysis of the Association Between Catechol-O-Methyltransferase and Response to a Randomized Open-Label Placebo Treatment for Cancer-Related Fatigue - Hoenemeyer, Teri W.; Baidwan, Navneet Kaur; Hall, Kathryn; Kaptchuk, Ted J.; Fontaine, Kevin R.; Mehta, Tapan S. (Frontiers in Psychiatry, 2021)
Previous studies have identified the gene, catechol-O-methyltransferase (COMT), as a primary regulator of sympathetic function. Although the COMT SNP rs4680 and rs4818, are well-studied, little is known about their influence on cancer-related fatigue (CrF) and placebo response. In this study, we examined whether genetic variation in COMT, at the functional SNP rs4680 and rs4818, influenced open-label placebo (OLP) responses found in cancer survivors reporting moderate to severe CrF and whether those responses differed by allele variation. We randomized cancer survivors (N=74) reporting moderate-to-severe CrF to receive OLP or to treatment-as-usual (TAU) and assessed if rs4680 and rs4818 were associated with changes in fatigue severity and fatigue-distressed quality of life. At the end of the initial 21 days, the treatments were crossed over and both groups were re-assessed. Decreases in fatigue symptom severity and fatigue-distressed quality of life across both genotypes (rs4680 and rs4818) were reported by participants when taking placebos. However, across all participants, only those with the high-activity G-allele (rs4680) and those with the rs4818 C/G combination reported significant decreases in fatigue severity and improvements in fatigue-distressed quality of life. Both COMT rs4680 high-activity G-allele and COMT rs4818 C/G were significantly associated with decreases in fatigue severity and improvements fatigue-distressed quality of life.